Synthesis and evaluation of the antifungal activity of aromatic hydrazones (2022)
Acylhydrazones have been studied since 1850, they are important compounds for drug design due to their extensive biological activity. The compounds were synthesized by a nucleophilic addition reaction to the carbonyl group; six derivatives were obtained using 2,4-dinitrophenylhydrazine (2,4-DNPH) and ketones: fluorenone, benzophenone and substituted benzophenones; Good yields have been obtained in all cases, the best percentage corresponds to compound (7), with 67% and the lowest to compound (10) with a yield of 29%. Principles number two and five of green chemistry were applied during the development of the synthesis. In addition, the production methodology used was a modification of the procedure described in the knowledge base. The substituted benzophenones were obtained by oxidation of the respective alcohols, so that it was obtained benzophenones and fluoenone; In this method, sodium hypochlorite is used as an oxidation agent and tetrabutyl ammonium bromide as a phase transfer medium in an aqueous medium. The molecules were characterized by proton nuclear magnetic resonance (1H-NMR) and attenuated total reflectance infrared spectroscopy (IR-ATR) among other spectroscopic techniques. Biological activity was evaluated by using the Kirby-Bauer method, in order to determine the sensitivity of an organism to antibiotics or antifungals. The results show that the substituted hydrazones (9 and 10) presented a higher inhibitory activity against Candida albicans and Aspergillus niger compared to 1% cycloheximide, but considerably less effective than ketoconazole compounds used as control.